Strategy for Strengthening Religious Moderation in Vocational Higher Education through Project-Based Learning - Afip Miftahul Basar; Ceceng Saepulmilah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
Strengthening religious moderation is a strategic priority in Indonesian higher education, including vocational institutions that emphasize practical and workforce-oriented learning. However, the integration of religious moderation in vocational education is often limited to normative approaches and lacks effective pedagogical implementation. This study aims to examine the effectiveness of Project-Based Learning (PBL) in strengthening students’ religious moderation attitudes in vocational higher education. This study employed a mixed-methods approach with a quasi-experimental pretest–posttest control group design using a sequential explanatory strategy. The participants were 59 second-semester students from the D3 Electrical Engineering and Installation program. Quantitative data were collected using a religious moderation attitude scale and analyzed through paired-samples t-tests and ANCOVA. Qualitative data were obtained from reflective journals, semi-structured interviews, and classroom observations, and analyzed thematically. The results indicate that students who participated in PBL-based Islamic Religious Education showed a statistically significant improvement in religious moderation attitudes compared to those who received conventional lecture-based instruction. Qualitative findings reveal that collaborative project work, exposure to diverse perspectives, and structured reflection played key roles in facilitating the internalization of moderation values. These findings suggest that Project-Based Learning is an effective and contextually relevant pedagogical strategy for strengthening religious moderation in vocational higher education, with implications for curriculum design and instructional practice.